Detailed shallow structure seismic refraction investigation, with the application of different processing techniques - ΠΑΠΑΔΟΠΟΥΛΟΣ Τ.; ΚΑΜΠΟΥΡΗΣ Π.; ΑΛΕΞΟΠΟΥΛΟΣ Ι. (Bulletin of the Geological Society of Greece, 2001)
A comparative study of conventional and modern processing techniques of seismic refraction data is examined in this paper, for shallow structure investigation in the framework of a geotechnical research. The techniques used here were applied for the detection of narrow and low seismic velocity zones along the bedrock in the 10.5th Km of the new national road Igoumenitsa-Ioannina. The results were comparable and only slight deviations were observed due mainly to different algorithm procedures applied on data and the resolution provided by each technique. It is pointed out that the non linear tomography seismic refraction technique, overcomes the conventional ones since by increasing the number of seismic sources and considering the gradual variation of seismic velocity with depth, a better resolution and image reconstruction for the subsurface structure is obtained.